2009
DOI: 10.1111/j.1748-3131.2009.01106.x
|View full text |Cite
|
Sign up to set email alerts
|

Demographic Change and Economic Growth in Asia

Abstract: Trade openness, high savings rates, human capital accumulation, and macroeconomic policy only accounted for part of the 1965-1990 growth performance in East Asia. Subsequently, demographic change was shown to be a missing factor in explaining the East Asian growth premium. Since 1990, East Asia has undertaken major economic reforms in response to financial crises and other factors. We reexamine the role of the demographic transition in contributing to cross-country differences in economic growth through to 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
225
2
8

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(253 citation statements)
references
References 17 publications
18
225
2
8
Order By: Relevance
“…Prskawetz et al (2007) suggests that a declining fertility rate can have a positive impact on economic growth. Bloom and Williamson (1998) identify two mechanisms through which this can occur. Both mechanisms revolve around the effect a declining fertility rate has on the ratio of working age population to total population.…”
Section: Demographics Negatively Impact Growthmentioning
confidence: 99%
“…Prskawetz et al (2007) suggests that a declining fertility rate can have a positive impact on economic growth. Bloom and Williamson (1998) identify two mechanisms through which this can occur. Both mechanisms revolve around the effect a declining fertility rate has on the ratio of working age population to total population.…”
Section: Demographics Negatively Impact Growthmentioning
confidence: 99%
“…Applying Input Variables, the speed of convergence was increasing which implied that ASEAN conditionally converged with the speed is 25.56%. Investment and openness had positive impact and population growth had negative influence as suggested in [12] that the association between population growth and per capita growth was negative for positive effects of scale and induced innovation. Government expenditure had no influence.…”
Section: Results a Productivity Convergencementioning
confidence: 99%
“…Feyrer [11] indicated that the change in workforce has a strong and significant impact on the growth rate of productivity and dependency ratio has no influence on productivity. Bloom and Finlay [12] found the significant of demographic transition in East Asia growth; labor force growth has significant and positive influence on growth as so working age population and life expectancy. Bloom, et al [3], investigating the impact of demographic change on growth, found that conditional income convergence existed both in China and India, working age population has positive impact on growth and so life expectancy.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…It has been argued that this dividend of lower child dependency and higher representation of adults in the prime working age groups played an important part in the rapid economic development of the 'East Asian Tigers', like South Korea and also China (Bloom et al 2000). The next phase, involving high and increasing representation of older people may, it has been suggested, also bring some economic benefit in the form of increased savings (by the large number of older people) and so greater capital available for investment (Mason and Lee 2006).…”
Section: Age Structurementioning
confidence: 99%